American Culture vs Self Construction in August Wilson’s King Hedley II - Hussein Dizayi, Assist. Prof. Dr. Saman A.; Tahi, Assist. Lect. Ary S. (Mitanni Journal of Humanitarian Sciences, 2022)
Culture in the United States during the 1980s has had a great influence on African American personalities, class, and gender. The play King Hedley II by August Wilson explores culture's influences through characters such as king, Mister, and Tonya. This paper will analyze how culture shapes the personality of people, individuals, class, and gender by closely examining how the environment has structured their traits and personalities. The paper also will cover elements such as violent environments contribution in affecting the African Americans lived during the 1980s. Furthermore, poverty level among the blacks, and racism which is attributed to the circumstances characters go through in their lives. Other aspects that would be examined necessitates the availability of opportunities for the African Americas and the possibility of hope to get out of the condition that African Americans found themselves in during the 1980s, as per the August play. The paper conducts a textual analysis through reading the play and investigating the cultural aspects that affected in shaping personalities of the characters. Finally the paper reaches at the point, among some, that the cultural environment directly influences both society and Individual’s self-construction.